Comprehensive analysis of motions in molecular dynamics trajectories of the actin capping protein and its inhibitor complexes. Issue 7 (16th April 2016) - Koike, Ryotaro; Takeda, Shuichi; Maéda, Yuichiro; Ota, Motonori
ABSTRACT: The actin capping protein (CP) binds to actin filaments to block further elongation. The capping activity is inhibited by proteins V‐1 and CARMIL interacting with CP via steric and allosteric mechanisms, respectively. The crystal structures of free CP, CP/V‐1, and CP/CARMIL complexes suggest that the binding of CARMIL alters the flexibility of CP rather than the overall structure of CP, and this is an allosteric inhibition mechanism. Here, we performed molecular dynamics (MD) simulations of CP in the free form, and in complex with CARMIL or V‐1. The resulting trajectories were analyzed exhaustively using Motion Tree, which identifies various rigid‐body motions ranging from small local motions to large domain motions. After enumerating all the motions, CP flexibilities with different ligands were characterized by a list of frequencies for 20 dominant rigid‐body motions, some of which were not identified in previous studies. The comparative analysis highlights the influence of the binding of the CARMIL peptide to CP flexibility. In free CP and the CP/V‐1 complex, domain motions around a large crevice between the N‐stalk and the CP‐S domain occur frequently. The CARMIL peptide binds the crevice and suppresses the motions effectively. In addition, the binding of the CARMIL peptide enhances and alters local motions around the pocket that participates in V‐1 binding. These newly identified motions are likely to suppress the binding of V‐1 to CP. The observed changes in CP motion provide insights that describe the mechanism of allosteric regulation by CARMIL through modulating CP flexibility. Proteins 2016; 84:948–956. © 2016 Wiley Periodicals, Inc.